Theoretical Studies of the Optical Properties of ZnS , ZnO and CdS Nanopartical Using the Brus Equation - Assim Ahmed Issa; Tamathir Abbas Hamoudi (Tikrit Journal of Pure Science)
In the present work, Brus equation has been used to study the size effect of the quantum dot on the optical properties of some semiconductor compounds ( CdS, ZnS and ZnO). It is found that the absorption wavelength and bandgap energy are dependent on the size of the QD. As the size of the QD decreases, the bandgap energy increases and the absorption wavelength decreases. There is good agreement of the theoretical results of the bandgap energy and absorption wavelength obtained in this study using Brus equation with the published experimental results for the semiconductor compounds mentioned above.